DEVELOPMENT OF INTERACTIVE LEARNING MEDIA WITH THE ASSISTANCE OF GOOGLE SITES ON ARRAY MATERIALS AT SMK NEGERI 1 MUARO JAMBI - Putri, Fadilla Risky; Wulandari, Bunga Ayu (Indonesian Journal of Educational Development (IJED), 2024)
One of the main learning problems is the tendency to lack appropriate and comprehensive content in interactive learning media. Array materials require a clear and complete explanation of the basic concepts, operations, and applications in programming. The purpose of this research was to develop interactive learning media and determine the level of feasibility and attractiveness in supporting the learning process. The research method used was Research and Development. The research subjects were students from SMK Negeri 1 Muaro Jambi. The alpha test results from multimedia experts amounted to a percentage of 80%, the learning media was considered feasible with the need for minor revisions and the data from the assessment by material experts which showed a very good category and obtained a percentage of 97.08%. The beta test data, namely the subject teacher's assessment of the learning media, obtained a percentage of 96% so that it could be categorised as feasible to use as a learning media and the results of the questionnaire of students in class X TKJ I and X TKJ II both obtained a percentage of 89% with a very feasible category. From the data obtained, it could be concluded that that Google site learning media on this array material could be used and supports the learning process.